PANDAWA: Inovasi Dinas Kependudukan dan Pencatatan Sipil Kabupaten Pasaman Barat dalam Memberikan Pelayanan Administrasi Kependudukan - Alifya, Falina; Ariany, Ria; Ekha Putera, Roni (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2024)
Quality public services are the hope of every society. Therefor, the West Pasaman Regency Population and Civil Registration Service strives to provide the best service through various service innovations, one of which is PANDAWA. PANDAWA is a digital innovation in providing population administration service via whatsapp so that people can access service online by sending massage to the PANDAWA whatsapp number. The research aims to analyze the attributes of PANDAWA innovation in providing public services. This research was elaborated using Evereet Rogers theory about innovation atributes . This research uses descriptive qualitative research methods. Meanwhile for data collection, researchers used three methods namely interviews, documentation, and observation. The research results obtained are that PANDAWA innovation provides benefits both in term of time and cost for community. This innovation is also relevant to the vision and mission of West Pasaman Regency and is ini accordance with previous innovations, namely DPM. As an innovation PANDAWA is generally not complicated to access, but there several types of service that require downloading a form as a requirement. Than, PANDAWA has also gone through a trial process and is easy information PANDAWA related to can be seen on the West Pasaman Disdukcapil Disdukcapil’s instagram, facebook, but teh available information is not update.